Incidencia de la gestión financiera en los márgenes de ganancia en la empresa Aguisoricom Cia. Ltda. - Tinoco Caminos, Fernando Misael; Espinoza Romero, Camila Lizbeth (Machala : Universidad Técnica de Machala, 2024)
Globally, inadequate financial management is a significant problem, especially in small and medium-sized enterprises. In this context, research was carried out to evaluate financial management and its impact on profit margins through the analysis of operational expenses planning and decision making. The objective is to analyze the impact of financial management on profit margins in the company AGUISORICOM CIA LTDA. by applying ratios to provide a comprehensive view of the financial situation. This research is based on an analytical-synthetic methodology with a positivist epistemological approach, also a mixed approach was adopted, combining quantitative and qualitative methods. The company's accountant was surveyed to determine her perception of the economic situation of the entity. The findings allowed identifying that the company faces an inefficient financial planning, with an increase of 21.08% in transportation expenses that reduced the profit by 2.03% and an over-indebtedness of 82.38%, compromising its solvency.
A nivel mundial, la inadecuada gestión financiera es un problema significativo especialmente en las pequeñas y medianas empresa. En este contexto se llevó a cabo la investigación para evaluar la gestión financiera y su impacto en los márgenes de ganancia mediante el análisis de la planificación de los gastos operacionales y la toma de decisiones. El objetivo es analizar la incidencia de la gestión financiera en los márgenes de ganancia en la empresa AGUISORICOM CIA LTDA. mediante la aplicación de ratios para proporcionar una visión integral de la situación financiera. Esta investigación se basa en una metodología analítica-sintética con un enfoque epistemológico positivista, además se adoptó un enfoque mixto, combinando método cuantitativos y cualitativos. Se realizó encuestas a la contadora de la empresa para determinar su percepción sobre la situación económica de la entidad. Los hallazgos permitieron identificar que la compañía enfrenta una planificación financiera ineficiente, con un incremento del 21,08% en gastos de transporte que redujo la utilidad en un 2,03% y un sobreendeudamiento del 82,38%, comprometiendo su solvencia.
Keywords: MARGENES DE GANANCIA; GESTION FINANCIERA; TOMA DE DECISIONES; RATIOS FINANCIEROS